Empirical Investigation of Industrial Management - Zahariev, Elenko (Journal of Economic Development, Environment and People, 2014)
The paper is devoted to an aspect in the sphere of management – business priorities of industrial management in XXI century. In modern times the actuality of treated problems is mainly laid into the necessities of the real management practice in industrial organizations and the need theoretical and applied knowledge to be offered to that practice which would allow it methodologically right and methodically correct to implement the corresponding changes in management of a concrete organization. Objects of analyses and evaluations are some fragmented approbations of theses using the corresponding instruments. The characteristic features of the organizations’ profiles and the persons interviewed participated in the investigation are summarized. The determining approaches for Bulgarian organizations are considered too. On the basis of the critical analyses the fundamental tasks are drawn which are inherent to contemporary industrial managers. Attention is paid to key management functions for an effective managerial process. An analysis of managers reaching the best results in industrial management is presented as well as when they are reached. Outlined are also specific peculiarities of industrial management in theRepublicofBulgariaand parameters of the level of productiveness in conditions of business globalization and priority forms in marketing of the ready product / service in XXI century. The results of the launched idea for the necessity to create a new International management architecture (NIMA) are determined – structure and structure defining parameters. The results of the investigation of main business priorities in industrial management are commented as well as expected problems in the process of functioning of industrial organizations in XXI century. At the end the corresponding conclusions are made in respect to the techniques used in determining effectiveness of industrial management in Bulgarian organizations.